ACTIVE LEARNING BY USING LEARNING MANAGEMENT SYSTEM (LMS) TO IMPROVE STUDENTS’ COMPETENCE IN WRITING - Wardani Dwi Wihastyanang; Daning Hentasmaka; Rosi Anjarwati (STKIP PGRI Jombang, 2015)
Nowadays the educational paradigm has changed from passive learning into activelearning where learners are actively involved in teaching and learning process. The use of LearningManagement System (LMS) in the internet is viewed appropriate to be applied in teaching Englishespecially the writing skill in which learners need more time and more exercises to improve theirskill. By using LMS the teaching and learning process is not only depend on the classroom meetingbut also can be done outside the classroom, anytime and anywhere. In this quasi-experimental research the researchers were eager to know the effectiveness of activelearning by using Learning Management System (LMS) in improving students’ writing skill,especially in argumentative writing. The data was analyzed by using ANCOVA and the analysiswas done by using SPSS version 20.The result of ANCOVA shows that the value of F-value is 5.505 and the significant value is .021which is less than .05 and the F-value is higher than F-table (3.94). It means that the alternativehypothesis (Ha) is accepted. Thus it can be concluded that teaching writing by using LearningManagement System (LMS) is more effective than conventional classroom meeting.